Guidelines for technology selection in intralogistics: a scientific approach - Božić, Mladen S.; Đurđević, Dragan B.; Dabić-Miletić, Svetlana A. (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: Intralogistics involves the organization, control, realization, and optimization of material and information flows within a technologically integrated system. The selection and application of appropriate material handling equipment (MHE) play a crucial role in shaping intralogistics systems. This paper aims to define guidelines for selecting MHE based on scientific research. The methodology implemented to achieve this goal comprises several fundamental steps. Methods: The initial step involves analyzing three typical groups of tasks in (intra)logistics systems: transshipment, internal transport, and production activities. The analysis focuses on identifying and describing key task parameters, such as the type of unit load, quantity, flow intensity, and the location and timing of task initiation and completion. Next, there is a step devoted to the analysis of relevant scientific research. The literature is searched according to specific criteria, such as publication year, keywords, and citation count, to form a database of relevant papers. The analysis focuses on identifying and linking the parameters of practical tasks with those described in the literature and on the characteristics of the MHE used to facilitate the selection of appropriate MHE for these tasks. Results: Following this, in the third step, the observed task is classified according to standard task types found in the literature.Conclusion: Finally, in the last/fourth step, regression analysis is applied to define the guidelines for MHE selection based on the frequency of use of specific MHE groups for certain task groups as described in the literature.
Keywords: intralogistics; MHE selection; transshipment; internal transport; production